The ‘Mikami’-Catalyst in Enantioselective Diels–Alder Reactions of Juglone-Based Dienophiles with Different 1-Oxygenated Dienes: An Investigation on the Substitution Pattern Dependent Regioselectivity - Böse, Dietrich; Frey, Wolfgang; Pietruszka, Jörg (Synthesis, 2014)
A mechanistic study investigating the substitution pattern depending regioselectivity of enantioselective BINOL-Ti-catalyzed Diels–Alder reactions of juglone-based dienophiles with 1-oxygenated dienes is reported. The different influences of residues both on the diene as well as on the dienophiles are investigated giving a detailed picture of their role on the regioselectivity.
Keywords: catalysis; Diels–Alder reaction; Lewis acids; regioselectivity; enantioselectivity